The versatile roles of odontogenic ameloblast-associated protein in odontogenesis, junctional epithelium regeneration and periodontal disease - Zhu, Sipin; Xiang, Chuan; Charlesworth, Oscar; Bennett, Samuel; Zhang, Sijuan; Zhou, Maio; Kujan, Omar; Xu, Jiake (Frontiers in Physiology, 2022)
Junctionalepithelium(JE)isavitalepithelialcomponentwhichformsanattachmenttothe toothsurfaceatthegingivalsulcusbytheadhesionofproteincomplexesfromitsbasallayer. DisruptionoftheJEisassociatedwiththedevelopmentofgingivitis,periodontaldisease,and alveolarboneloss.Odontogenicameloblast-associated(ODAM),alsocalledAPINis comprisedofasignalpeptideandanODAMproteinwith12putativeglycosylationsites.It isexpressedduringodontogenesisbymaturationstageameloblastsandisincorporatedinto theenamelmatrixduringtheformationofouterandsurfacelayerenamel.ODAM,asa secretedproteinwhichisaccumulatedattheinterfacebetweenbasallaminaandenamel, mediatestheadhesionoftheJEtothetoothsurface;andisinvolvedwithextracellular signallingofWNTandARHGEF5-RhoA,aswellasintracellularsignallingofBMP-2- BMPR-IB-ODAM.ODAMisalsofoundtobehighlyexpressedinsalivaryglandsand appearstohaveimplicationsfortheregulationofformation,repair,andregenerationofthe JE.Bioinformaticsandresearchdatahaveidentifiedtheanti-cancerpropertiesofODAM, indicatingitspotentialbothasaprognosticbiomarkerandtherapeutictarget.Understanding thebiologyofODAMwillhelptodesigntherapeuticstrategiesforjunctionalepithelium regeneration,dentaldisordersandODAM-relateddiseases.